A comparative study on the level of motivation between students of different academic performance / Jurlina Sabang - Sabang, Jurlina (Faculty of Education, 2012)
This research was carried out as a descriptive survey to compare the level of motivation towards students of different level of academic performance. This study was conducted among Part 1 students of Faculty of Education, University Teknologi Mara, Seksyen 17 Shah Alam. The purpose of this research is to identify the level of motivation among students who had different academic achievements or CGPA. Hence, 30 of TESL students had been selected to answer the questionnaire given. There are 39 questions excluding questions in demographic background. The questionnaire form was divided into four sections which seek details on students' background, level of motivation, attitudes towards academic study(intrinsic motivation) and external Factors that influence students motivation. The data was analyzed interpreted and presented in the form of tables using Statistical Package for Social Sciences (SPSS) Version 17.0. These analysis included the application of frequency analysis, descriptives analysis, t test independent samples, and Pearson correlation. Based on the finding, it can be concluded that, in term of level of motivation, there were no significant difference between male and female students, and between students with high and average academic performance. It was also found that, Part 1 students from Faculty of Education, UiTM Shah Alam are encourage by external motivation rather than internal motivation. Lastly, parents and teachers play an important role in enhancing students motivation to learn.